2021
DOI: 10.1111/papt.12364
|View full text |Cite
|
Sign up to set email alerts
|

Working together: An investigation of the impact of working alliance and cohesion on group psychotherapy attendance

Abstract: Objectives Group psychotherapy holds considerable potential for cost‐effective treatment delivery. However, issues with client attendance can compromise the efficacy of such treatments. To date, client specific factors are amongst the most researched predictors of attendance in psychotherapy, with much less of a focus given to process factors, particularly in the group therapy context. This study aimed to determine which process factors influenced attendance in the context of a group therapy programme for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Group cohesion was high throughout the treatment and was not different between placebo versus treatment, suggesting that any difference in the scores of one module versus another was not due to improvements in cohesion. These findings support our hypothesis that emotional dysregulation lessened due to skills taught in DBT group sessions rather than simply group cohesion effects, to which research in group therapy has attributed a good amount of responsibility (Clough et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Group cohesion was high throughout the treatment and was not different between placebo versus treatment, suggesting that any difference in the scores of one module versus another was not due to improvements in cohesion. These findings support our hypothesis that emotional dysregulation lessened due to skills taught in DBT group sessions rather than simply group cohesion effects, to which research in group therapy has attributed a good amount of responsibility (Clough et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In self-report studies on Yalom's therapeutic factors, "cohesion" is considered the main therapeutic factor which facilitates the other therapeutic factors [29]. More recent authors have confirmed that "cohesion" can represent one of the prevalent therapeutic factors in a group [18,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The group therapist in a hospital setting has to adopt an active posture working to facilitate some small changes within the group, using the technique of "here and now". He performs the important function of guardian in regulating the impact of potentially negative extra-group factors, such as the extreme variability of patients sometimes discharged before their participation in the group or the devaluation of the therapeutic group within the ward, and has the duty to address these issues, ensuring that they do not permeate within the group and diminish the experience [9,13,17,18]. A meta-analytic review highlighted that beneficial effects were found for inpatient group therapy, with different effectiveness related to different psychiatric disorders [19].…”
Section: The Group Therapy In Acute Psychiatric Settingmentioning
confidence: 99%
“…However, upon further exploration, Reed determined that when group members’ scores were considered as a collective, the measures of cohesion in a group were correlated with higher measures of success related to the reduction of child problem behaviors. Though group therapy may not be the focus of CPRT, research has found a strong relationship between group cohesion, attendance, satisfaction with group, and treatment outcomes (Clough et al, 2022; Tucker et al, 2020) indicating selection and success in group may be enhanced with intake and recruitment protocols in CPRT. Further, when members do not feel comfortable with all members of the group, they are less likely to feel safe in engaging (Kinsworthy & Garza, 2010).…”
Section: Factors Impacting Viability and Effectiveness Of Cprtmentioning
confidence: 99%